2017
DOI: 10.1002/ajcp.12193
|View full text |Cite
|
Sign up to set email alerts
|

Community Data Collection with Children of Mothers Living withHIV: Boundaries of the Researcher Role

Abstract: The TRACK-II program is a multi-site, community-based randomized controlled trial evaluating an intervention to assist mothers living with HIV (MLH) in disclosing their HIV status to their young children. Many participants—both mothers and children—reported significant depression and/or suicidal ideation, a phenomenon that presented ethical challenges. This article focuses on participants at one site (Atlanta). Through the vignette of “Jordan,” we describe ethical challenges that may arise when faced with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…They outline the careful, step‐by‐step decision‐making process through which they created a system of proactive outreach to students that protected their privacy and respected their autonomy. Similarly, in LeCroix, Goodrum, Hufstetler, and Armistead's (2017*) randomized‐control evaluation of a community intervention for mothers living with HIV, many of the mothers and children disclosed significant depression and/or suicidal ideation. LeCroix and colleagues worked with their local IRB to develop a safety protocol that would connect participants to community resources, but they worried whether such efforts were sufficient.…”
Section: Beneficencementioning
confidence: 97%
“…They outline the careful, step‐by‐step decision‐making process through which they created a system of proactive outreach to students that protected their privacy and respected their autonomy. Similarly, in LeCroix, Goodrum, Hufstetler, and Armistead's (2017*) randomized‐control evaluation of a community intervention for mothers living with HIV, many of the mothers and children disclosed significant depression and/or suicidal ideation. LeCroix and colleagues worked with their local IRB to develop a safety protocol that would connect participants to community resources, but they worried whether such efforts were sufficient.…”
Section: Beneficencementioning
confidence: 97%
“…Scholars disagree about the appropriate boundaries of the researcher–participant relationship and what they can and cannot provide for participants who demonstrate significant need for supports and services (Kendall & Halliday, 2014). For example, in their study of mothers living with HIV and their children, LeCroix, Goodrum, Hufstetler, and Armistead (2017) struggled with this issue when they found that child participants endorsed suicidal ideation at higher rates than anticipated. Although researchers involved in the study were clinically trained to respond to these mental health needs, the research team determined that such interventions were outside their roles as researchers.…”
Section: A Trauma-informed Approach To Data Collectionmentioning
confidence: 99%
“…For example, the researchers may be surprised by unexpectedly high levels of suicidal behaviors in their samples. LeCroix et al (2017) found in a study about mothers living with HIV and their children, that the latter endorsed suicidal ideation at higher rates than anticipated by the research team. Although the study team was trained to respond to these mental health needs, the researchers determined that such interventions were outside their research roles.…”
Section: Infusing the Ti Model Into Suicide Researchmentioning
confidence: 78%